Achievement of Stunting-Free Status Tisnogambar Village Bangsalsari Subdistrict, Jember Regency - hikmah, Faiqoh Nurul Hikmah (Rumah Jurnal, University of Jember, 2025)
Stunting is a significant chronic nutritional problem in Indonesia, including in East Java, which affects children's growth and development. This study aims to explore the factors that influence stunting and its mitigation. Stunting is caused by inadequate nutritional intake, especially during the first 1000 days of life, as well as infections, poor sanitation and family economic conditions. Although the prevalence of stunting in East Java has decreased from 23.5% in 2021 to 19.2% in 2022, this figure still indicates that many children are affected. Effective nutrition interventions, such as multi-nutrient supplementation, nutrition education, and adequate nutrition support, are needed to improve children's nutritional status and reduce the risk of stunting. Research by Yudho Bawono et al. (2024) showed that socialisation on the impact of stunting increased community knowledge by 6.20%, confirming the importance of education in stunting prevention at the community level. In addition, the nutritional condition of the mother during pregnancy also plays an important role in the risk of stunting in children. Nutrient deficiencies such as iron and vitamin D during pregnancy can lead to low birth weight and stunting. Therefore, a comprehensive approach, involving education, access to health services, and collaboration between the government and the community, is essential to ensure children receive adequate nutrition and can grow optimally. This study is expected to provide deeper insights into the factors that influence stunting and the effectiveness of prevention efforts that have been made.